2012
DOI: 10.1016/j.devcel.2011.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Different Auxin Response Machineries Control Distinct Cell Fates in the Early Plant Embryo

Abstract: The cell types of the plant root are first specified early during embryogenesis and are maintained throughout plant life. Auxin plays an essential role in embryonic root initiation, in part through the action of the ARF5/MP transcription factor and its auxin-labile inhibitor IAA12/BDL. MP and BDL function in embryonic cells but promote auxin transport to adjacent extraembryonic suspensor cells, including the quiescent center precursor (hypophysis). Here we show that a cell-autonomous auxin response within this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
191
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(209 citation statements)
references
References 51 publications
6
191
0
1
Order By: Relevance
“…A major challenge for auxin biologists is to explain how a small molecule such as IAA can trigger the vast range of intricate, complex, and tissue-specific responses throughout plant development (Paciorek and Friml, 2006;Teale et al, 2006;Benjamins and Scheres, 2008;Vanneste and Friml, 2009;Rademacher et al, 2012;Enders and Strader, 2015;Hagen, 2015). We have recently shown that the atypical auxin response factor ETT responds to changes in cellular auxin levels in a different way from the canonical TIR1-dependent auxin-signaling pathway (Simonini et al, 2016), thus providing an additional route for auxin to mediate its diverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major challenge for auxin biologists is to explain how a small molecule such as IAA can trigger the vast range of intricate, complex, and tissue-specific responses throughout plant development (Paciorek and Friml, 2006;Teale et al, 2006;Benjamins and Scheres, 2008;Vanneste and Friml, 2009;Rademacher et al, 2012;Enders and Strader, 2015;Hagen, 2015). We have recently shown that the atypical auxin response factor ETT responds to changes in cellular auxin levels in a different way from the canonical TIR1-dependent auxin-signaling pathway (Simonini et al, 2016), thus providing an additional route for auxin to mediate its diverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Auxins comprise a class of plant hormones including the predominant auxin, indole-3-acetic acid (IAA), which is involved in an exceptional range of developmental processes during organ growth and differentiation (Benjamins and Scheres, 2008;Vanneste and Friml, 2009). In the nucleus, high auxin levels cause degradation of the Aux/IAA repressors, allowing auxin response factors (ARFs) to regulate transcription of their target genes in a signaling cascade that culminates in a myriad of different pathways (Vernoux et al, 2011;Rademacher et al, 2012;Calderón-Villalobos et al, 2012;Weijers and Wagner, 2016). The Arabidopsis thaliana genome encodes 23 ARFs and the N-terminal region of each ARF possesses a conserved DNA binding domain (DBD) able to mediate ARF dimerization and recognize auxin response elements (AuxREs) with the general sequence motif TGTCNN.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, endogenous auxin, zeatin and ABA were at high levels in highly regenerable rice callus (Liu and Lee 1996;Huang et al 2012). Auxin might be the main factor controlling cell differentiation (Bassuner et al 2007;Petrásek and Friml 2009;Rademacher et al 2012). Our previous studies indicated that endogenous auxin levels in rice calli may play critical roles during shoot regeneration (Huang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the non-cell-autonomous ARF3-mediated down-regulation of DR5::GUS activation in stigma epidermal cells suggests that ARF3 modulates a second auxin response cascade that acts cell-autonomously in these cells. Such interplay between non-cell-autonomous and cell-autonomous auxin response modules has been described in hypophysis specification (25). At present, it is not known if the down-regulation of ARF3 downstream targets and the dampening of a cell-autonomous auxin response cascade in stigma epidermal cells are two separate consequences of ARF3 activity or if suppression of the proposed mobile signal in turn down-regulates the cell-autonomous auxin response in the stigma epidermis.…”
Section: Discussionmentioning
confidence: 95%